A province under pressure: climate change policy in Alberta - Boyd, Brendan (My University, 2019)
Alberta is responsible for over a third of Canada's greenhouse gas (GHG) emissions. Reducing the country's emissions requires policies and initiatives that reduce emissions in the province. Yet the study of provincial climate change policy in Canada has largely focused on lower-emitting provinces like British Columbia, Quebec and Ontario. This article argues that Alberta is best understood as a “reluctant actor” on climate change, whose policies are influenced by decisions and pressures from outside its borders. The literature on Canadian-American environmental policy making and international policy transfer are used to explore provincial GHG targets and carbon pricing policies. The article finds that Alberta's 2002 targets and Specified Gas Emitters Regulation were determined by economic competitiveness and leakage concerns, while the adoption of new GHG targets in 2008 and a carbon tax was the result of policy transfer through political bandwagoning and the desire for reputational benefits.
Keywords: Alberta; greenhouse gas; GHG; climate change; carbon tax; Canadian-American environmental policy; carbon pricing policies; Gas Emitters Regulation